Management of Financial Inclusion in Islamic Banking: Evidence From Indonesia - Reksa Ahmad Jayengsari; Uus Ahmad Husnaeni (Universitas Muhammadiyah Prof. DR HAMKA., 2020)
Financial inclusion aims to encourage unbankable people to have access to the formal financial system, so they have the opportunity to access financial services from savings, payments, financing, insurance, and various other financial services. Therefore, the implementation of financial inclusion becomes an urgent matter in the context of poverty alleviation. The purpose of this research is to analyze the role of sharia banking in implementing financial inclusion in Indonesia. This research is a descriptive research with qualitative approach. Sources of data used are primary and secondary data. Primary data are interview result with Bank Indonesia, Financial Services Authority (OJK) and Islamic bank. Secondary data in the form of financial statements of Islamic bank year 2013-2017. Qualitative data analysis using techniques developed by Miles and Huberman, namely data reduction, display data, and conclusion drawing. This research is strengthened by quantitative data analysis using financial report analysis technique and ratio analysis from CAR, ROA, ROE, NPF, and FDR of Islamic bank. The conclusion of this research is that Islamic bank has big potential in implementing financial inclusion in Indonesia as evidenced by the increase of Third Party Fund (DPK) and increasing financing, especially micro financing, plus zakat fund and social fund which enable to give access to small and micro business unbankable people. Policy support that is responsive and synergic to stakeholders can help to accelerate the implementation of financial inclusion in Indonesia.